MANIFESTATION OF WILL-POWERED QUALITIES IN THE ACTIVITY OF A PROFESSIONAL PSYCHOLOGIST - Mirashirova Nargiza Anvarovna; Ashurmatov Muzaffar Komilovich (Bright Mind Publishing, 2025)
This article analyzes the manifestation of volitional qualities in professional activity, the impact of this process on the professional psychologist's activity, and the results of empirical research on the study of volitional qualities.
Keywords: Professional psychologist, professional activity, volitional qualities, responsibility, initiative, courage, independence, persistence, determination, enthusiasm, attentiveness, purposefulness.